2013
DOI: 10.1515/nleng-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Flow Through a Converging-Diverging Micro-Nozzle

Abstract: Cold spray is a material deposition process used to deposit metallic features for use in applications such as corrosion prevention, dimensional correction and repair, and wear resistant coatings. Micro Cold Spray Direct Write (MCS-DW) is a variant of the cold spray process in which metal particles are accelerated and focused to print fine features on flexible and rigid substrates with no postprocessing required. This paper presents results of numerical studies on the flow of 2 µm and 6 µm diameter silver parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…It is worth noting that in the paper (Bhattacharya et al, 2013) they found that the Saffmann force causes an increase in focusing of the particles.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…It is worth noting that in the paper (Bhattacharya et al, 2013) they found that the Saffmann force causes an increase in focusing of the particles.…”
Section: Introductionmentioning
confidence: 93%
“…See, e.g., paper by Ling et al (2011), in which the situation where the unsteady contribution of force can be significant is considered in details. However, if the density of the carrier phase is considerably lower than that of the dispersed phase and particles do not interact with shock waves but gradually gain speed due to the accelerating carrier flow, then all of the forces except for drag and, possibly, the Saffman force become negligibly small (see, in particular, an analysis performed in (Bhattacharya et al, 2013)).…”
Section: Dispersed Phase Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The MCS system was developed similar to our work with CAB-DW where we utilized a model for fluid-particle interaction combining Stokes, Saffman, and when appropriate Magnus forces to design optimum flow conditions and nozzle geometries for specific processes. [7][8][9] In our recent work, we have shown the ability to print copper traces on glass substrates with near-bulk conductivity without postprocessing, and line widths below 50 µm with MCS. [7] In this paper, we will describe to you the most recent results with printing copper and silver for applications as the top metallization layer of silicon heterojunction solar cells.…”
Section: Introductionmentioning
confidence: 99%